A phase II single-arm study of induction chemotherapy with cisplatin and gemcitabine followed by concurrent cisplatin and gemcitabine with thoracic radiation for unresectable locally advanced non-small cell lung cancer. (May 2013) - Driesen, Peter; Lambrechts, Marc; Kraaij, Kees; Soldatenkova, Victoria; Chouaki, Nadia; Colinet, Benoit
Objectives: The aim of this study was to evaluate the efficacy and tolerability of the combination of cisplatin–gemcitabine with concurrent thoracic radiotherapy for locally advanced non-small cell lung cancer (LA-NSCLC). Methods: This was a phase II, multicenter, open-label, single-arm trial in treatment-naïve patients with stage IIIA and IIIB LA-NSCLC. After three induction cycles with gemcitabine 1250 mg/m 2 plus cisplatin 80 mg/m 2, two concurrent chemoradiotherapy cycles with gemcitabine 300 mg/m 2, cisplatin 80 mg/m 2, and radiotherapy (63 Gy) were administered. The primary endpoint was response rate after induction chemotherapy followed by concurrent chemoradiotherapy. Secondary endpoints included time to progressive disease (TtPD), overall survival (OS), and safety. Results: Overall, 49 patients (median age 63.4 years; 73.5% male; Karnofsky performance status scores of 80, 85, 90, and 100 [16.3%, 2.0%, 49.0%, and 32.7%, respectively]; disease stage IIIA or IIIB 28.6% and 71.4%, respectively) were enrolled and treated. Response rate was 38.8% (95% confidence interval [CI] 25.2–53.8%). Median TtPD was 11.4 months (95% CI 9.4–12.9). Median OS was 21.8 months (95% CI 17.5–26.0), with 1- and 2-year survival rates of 70.8% and 43.7%, respectively. Overall, six patients discontinued from study treatment due to adverse events (AEs), of which two were serious AEs. The most relevant grade 3/4 AEs were neutropenia and thrombocytopenia in induction chemotherapy and chemoradiotherapy, and grade 3 events related to radiation in acute chemoradiotherapy, e.g. dysphagia, radiation pneumonitis, and radiation esophagitis. Conclusions: Induction chemotherapy followed by concurrent chemoradiotherapy with gemcitabine (300 mg/m 2 ) and cisplatin was associated with acceptable toxicity. The observed median OS time was 21.8 months. Response evaluation was difficult as in many cases it was not possible to differentiate tumor progression from local radiofibrosis.